PENERAPAN MODEL MAKE A MATCH DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BILANGAN ROMAWI PADA SISWA KELAS IV SDN 3 KARANGSAMBUNG TAHUN AJARAN 2012/2013 - WAN, MISWAN (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Application of Models Make a Match in Mathematics Learning Enhancement increasing number of roman in Class IV elementary school. This study aims to improve mathematics learning increasing number of roman in class IV by applying the model to Make a Match. The experiment was conducted in three cycles. The subjects were all fourth grade students of SD Negeri 3 Karangsambung totaling 28 students. Data came from students, peers, and researchers. Data collection techniques using observation, testing and documentation. Analysis of the data using description qualitative and quantitative. The result of study aims are percentage of completeness student learning outcomes in the first cycle was 85.71%, 89.23% second cycle and third cycle was 92.86%. The conclusions shows that the application of the model to Make a Match, can improve student learning in mathematics learning increasing number of roman in class IV elementary school. Keywords: Make a Match, Learning, Mathematics, Number of Roman. Abstrak: Penerapan model Make a Match dalam peningkatkan pembelajaran Matematika tentang bilangan romawi pada siswa Kelas IV SD. Penelitian ini bertujuan untuk meningkatkan pembelajaran Matematika tentang bilangan romawi pada siswa kelas IV SD dengan menerapkan model Make a Match. Penelitian dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah siswa kelas IV SD Negeri 3 Karangsambung yang berjumlah 28 siswa. Data berasal dari siswa, teman sejawat, dan peneliti. Teknik pengumpulan data menggunakan observasi, tes dan dokumentasi. Analisis data menggunakan deskripsi kualitatif dan kuantitatif. Hasil penelitian yaitu Persentase ketuntasan hasil belajar siswa pada siklus I adalah 85,71%, siklus II 89,23%, dan siklus III adalah 92,86%. Simpulan penelitian ini adalah penerapan model Make a Match, dapat meningkatkan pembelajaran Matematika tentang bilangan romawi pada siswa kelas IV SD. Kata Kunci: Make a Match, Pembelajaran, Matematika, Bilangan Romawi.